Microenvironment derived from metanephros transplantation inhibits the progression of acute kidney injury in glycerol-induced rat models. Issue 1 (1st January 2020) - Li, Kailin; Chen, Yuan; Zhang, Jianye; Guan, Yong; Sun, Chao; Li, Xian; Xie, Xiaoshuai; Zhang, Denglu; Yu, Xin; Liu, Tongyan; Zhang, Xufeng; Kong, Feng; et al.
Abstract: Background: Embryonic metanephros is the mammalian renal anlagen, which is considered as a potential source for the regeneration of functional whole kidneys. Some studies reported that metanephros implanted into unilateral nephrectomized animals can develop into kidney tissue. However, kidneys are nephrotoxic in renal failure patients, and whether metanephros can grow in nephrotoxic has not been reported. This study aims to investigate the growth of metanephros in acute nephrotoxic environment and analyze the therapeutic effect of metanephros microenvironment on acute kidney injury (AKI). Methods: AKI was induced in 200 g Wistar rats by giving intramuscular injections of 50% glycerol (10 mL/kg) in their hind limbs. 45 rats were divided randomly into three groups (control, glycerin, and metanephros). Metanephros group was transplanted two metanephroi (embryonic day 15) into the renal capsule of AKI rats. Glycerin group was AKI rats without transplantation. Control group was untreated. Results: Mature glomeruli and tubules were detected in the grafts in metanephros group, which means that metanephroi can grow into tissues with mature kidney structure under acute nephrotoxic. Then, we assessed the renal function of host rats and found that there were fewer tubular necrosis in metanephros group than glycerin group, and the serum creatinine and urea nitrogen were significantly lower in metanephros group than glycerin group. Conclusion: These results suggested that embryonic metanephroi can grow into tissues with mature kidney structure under acute nephrotoxic, and the graft microenvironment was effective in inhibiting the progression of AKI, which provides a new approach for the treatment of acute renal injury.